Accessibility of Informal Workers in Batu City to Social Security Programs during the COVID Pandemic - Dewi Puspita Rahayu; Genta Mahardika Rozalinna; Lutfi Amiruddin (Journal of Research in Social Science and Humanities, 2025)
The COVID-19 pandemic has significantly impacted informal workers in Batu City, particularly in accessing employment social security. This study aims to measure the accessibility level of informal workers to BPJS Ketenagakerjaan during the pandemic and identify the supporting and inhibiting factors. Using a descriptive quantitative method through a survey of 438 respondents, the findings indicate that the accessibility of informal workers remains moderate. The main obstacles include a lack of socialization regarding BPJS Ketenagakerjaan and the perceived burden of insurance premiums amid declining incomes due to the pandemic. These findings highlight the need for strategic policies to improve the accessibility of social security for informal workers, especially in times of crisis.